4CPS-181 Budgetary impact of biosimilar prescription in the treatment of rheumatic diseases. (24th March 2020) - Linares, A; Fernandez Cuerva, C; Asensi Diez, R; Muñoz Castillo, I
Abstract : Background and importance: Biological medicines for the treatment of rheumatological diseases requires a large budget in our hospital as the number of patients and drugs involved increase each year, making it essential to implement containment policies. Our pharmacy service has promoted biosimilar prescriptions in order to improve the efficiency of our health system. Aim and objectives: To evaluate the economic impact on the cost per patient of the use of biological products in the area of rheumatology since the implementation of biosimilar drug prescriptions. Material and methods: A retrospective analysis of pharmaceutical expenditure for biological drugs prescribed for rheumatological pathologies was conducted from January 2016 to December 2018. Data collected were budget, biological therapies and number of patients treated. Data were collected from electronic prescribing and economic software (Athos). Results: During the study period, 1704 patients received biological drugs prescribed by the rheumatology service, which supposed an expenditure of 13 904 349.46€. Therapies prescribed were: etanercept (36.03%), adalimumab (18.99%), golimumab (14.43%), tocilizumab (12%), infliximab (9.31%) and certolizumab (6.24%); abatacept, ustekinumab, rituximab and anakinra were prescribed in <1% of patients. In 2017, biosimilar prescriptions in rheumatology were promoted in such a way that the start of treatment (naive patients) had to be performed with a biosimilar medicine. This strategy began with infliximab and etanercept, and supposed a growth in the percentage of prescribed biosimilars. In 2018 versus 2017, the percentages of inliximab biosimilar were 35% versus 18%. In 2018 versus 2017, the percentages of etanercept biosimilar were 55% versus 21%. By the end of 2018, adalimumab biosimilar started to be prescribed, reaching 2% of all prescriptions of adalimumab. Table 1 shows the evolution for biologics expenditure in rheumatology. Conclusion and relevance: Biosimilar prescription strategies in rheumatology have led to an increase in the number of patients treated with a cost/patient/month reduction of approximately 25%. More patients have been treated each year with the same annual budget which reinforces the importance of the biosimilar prescription. References and/or acknowledgements: 1. Grupo de trabajo de la GUIPCAR. Guía de Práctica Clínica para el Manejo de Pacientes con Artritis Reumatoide . Madrid. Sociedad Española de Reumatología. 2019. (Accessed October 2019). Available at: https://www.ser.es/wp-content/uploads/2019/04/Guia-de-Practica-Clinica-para-el-Manejo-de-Pacientes-con-Artritis-Reumatoide.pdf No conflict of interest.